2020
DOI: 10.1109/access.2020.3000068
|View full text |Cite
|
Sign up to set email alerts
|

Intelligent Diagnosis for Railway Wheel Flat Using Frequency-Domain Gramian Angular Field and Transfer Learning Network

Abstract: The intelligent diagnosis of wheel flat based on vibration image classification is a promising research subject for performance maintenance of railway vehicles. However, the image representation method of vibration signal and classification network construction under small samples have become two obstacles to intelligent diagnosis of wheel flat. This paper presents a novel frequency-domain Gramian angular field (FDGAF) algorithm to encode the vibration signal of wheel flat to featured images. Furthermore, a mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 29 publications
1
24
0
Order By: Relevance
“…By assessing related work concerning these three dimensions, it can be seen that studies are either restricted to one dataset, belonging to one isolated domain [35], [38], only base their findings on a single visualization technique [39], or are built upon a small sample size [31], manifesting limited validity and do not allow to expand proposed approaches to classification problems with an insufficient sample size [34]. As studies have shown that using non-raw data and including manual feature extraction is highly time-consuming [17] and includes the risk of wrongfully classifying relevant features in the time-series data [12], [16], the state-of-research manifests high potential for improvement of objectivity and efficiency.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…By assessing related work concerning these three dimensions, it can be seen that studies are either restricted to one dataset, belonging to one isolated domain [35], [38], only base their findings on a single visualization technique [39], or are built upon a small sample size [31], manifesting limited validity and do not allow to expand proposed approaches to classification problems with an insufficient sample size [34]. As studies have shown that using non-raw data and including manual feature extraction is highly time-consuming [17] and includes the risk of wrongfully classifying relevant features in the time-series data [12], [16], the state-of-research manifests high potential for improvement of objectivity and efficiency.…”
Section: Related Workmentioning
confidence: 99%
“…However, despite industries increasingly implementing sensor devices [5] and more than 65% of the Fortune 1000 companies already using benchmarking to obtain competitive advantages [29], [37], the current state of research lacks a systematic evaluation on how varying these time-series imaging-related dimensions influence the classification performance across domains. Studies are either adapted to a specific domain [38], only use a single visualization technique [39], manifest a small sample size [31], or manifest the theoretical issue of long-term dependencies as their approaches are based on RNNs [40], [41]. Therefore, related work is limited either theoretically [40], [41] or practically [35], [38], [39] regarding the systematic analysis of raw time-series data across domains.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In [17], a data driven approach to estimate the length of a wheel flat is proposed. Bai et al [18] presented a frequency-domain image classification method to analyze wheel flats.…”
Section: Introductionmentioning
confidence: 99%
“…Chen, Wang 18 presented that fault diagnosis should be changed from behavioral research to mechanism research, and emphasized the importance of dynamic analysis and signal processing. Although PHM technology including reliability evaluation 19 and fault diagnosis 20 can greatly improve the safety of railway vehicles, dynamic modeling is still the basis of health management of railway vehicles for better understanding the fault mechanism. 21 The accurate and straightforward fault modeling and effective signal processing method is the key to realize the vibration feature analysis of faults of axlebox bearing of a railway vehicle.…”
Section: Introductionmentioning
confidence: 99%